The Implementation of Three-Language Assembly Program in Fostering Language Culture at MTsN 2 Mandailing Natal - Ayu Meita Puteri Siregar; Rony Mauli Bintang Rambe; Riski Rahmadani; Salsabila Az-Zahra; Siti Aisyah; Ilza Vanila (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the implementation of the Three-Language Assembly Program in fostering language culture at MTsN 2 Mandailing Natal. This program is a habituation strategy that rotates the use of Indonesian, Arabic, and English during morning assemblies to create a multilingual and character-oriented educational environment. The research employed a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews with 25 informants consisting of the principal, vice principal, teachers, and students, as well as documentation. Data analysis utilized the interactive model including data condensation, data display, and conclusion drawing. The findings reveal that the program is systematically implemented through teacher mentoring, a rotating officer system, and regular evaluations. This initiative contributes to improving students' speaking skills, self-confidence, and character development, while simultaneously strengthening their religious, national, and global identities. The main supporting factors include the consistency of the language environment and active teacher involvement, whereas challenges involve public speaking anxiety, limited vocabulary, and the suboptimal use of foreign languages outside assembly activities. These findings confirm that consistent practice and institutional support are keys to the program's success in fostering language culture in madrasah settings